2019
DOI: 10.1038/s41586-019-1707-0
|View full text |Cite
|
Sign up to set email alerts
|

FSP1 is a glutathione-independent ferroptosis suppressor

Abstract: Ferroptosis is an iron-dependent form of necrotic cell death marked by oxidative damage to phospholipids 1,2. To date, ferroptosis has been believed to be restrained only by the phospholipid hydroperoxide (PLOOH)-reducing enzyme glutathione peroxidase 4 (GPX4) 3,4 and radicaltrapping antioxidants (RTAs) 5,6. The factors which underlie a given cell type's sensitivity to ferroptosis 7 is, however, critical to understand the pathophysiological role of ferroptosis and how it may be exploited for cancer treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
1,913
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,121 publications
(1,949 citation statements)
references
References 38 publications
25
1,913
3
8
Order By: Relevance
“…While additional work will be necessary to illuminate precisely how CoAdependent processes contribute to suppression of ferroptosis, one potential model is that inhibition of GSH elevates the amount of cysteine available for the production of CoA, and by extension downstream metabolites that regulate detoxification of lipid ROS species. This model is strongly supported by the previous discovery of the ferroptosis inducer FIN56 (37), which inhibits synthesis of mevalonate-derive products such as CoQ 10 , and the recent identification of a glutathione-independent suppressor of ferroptosis, FSP1, which catalyzes the reduction CoQ 10 to directly quench lipid peroxyl radicals (38,39).…”
mentioning
confidence: 71%
“…While additional work will be necessary to illuminate precisely how CoAdependent processes contribute to suppression of ferroptosis, one potential model is that inhibition of GSH elevates the amount of cysteine available for the production of CoA, and by extension downstream metabolites that regulate detoxification of lipid ROS species. This model is strongly supported by the previous discovery of the ferroptosis inducer FIN56 (37), which inhibits synthesis of mevalonate-derive products such as CoQ 10 , and the recent identification of a glutathione-independent suppressor of ferroptosis, FSP1, which catalyzes the reduction CoQ 10 to directly quench lipid peroxyl radicals (38,39).…”
mentioning
confidence: 71%
“…iFSP1 was identified as a potent FSP1 inhibitor and can trigger ferroptosis in GPX4 knockout cells that overexpress FSP1 (Figure 1). 63…”
Section: Fsp1-nad(p)h Pathway In Ferroptosismentioning
confidence: 99%
“…In addition to the canonical glutathione-based GPX4 pathway, a recent study showed that the ferroptosis supresor protein 1 (FSP1) targets ubiquinone in the plasma membrane and reduces it to ubiquinol in order to protect cells from lipid peroxidation and ferroptotic cell death (Bersuker, Hendricks et al, 2019, Doll, Freitas et al, 2019 A key step in ferroptosis execution is the final disruption of the plasma membrane, which mediates the release of intracellular factors acting as DAMPs. However, the molecular mechanism causing the loss of plasma membrane integrity during ferroptosis remains completely unsettled and the nature and size of the membrane injury in ferroptosis has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%